Penanganan Ikterus Fisiologis pada Bayi Baru Lahir Melalui Terapi Jemur Pagi - Putri Handayani; Nevi Susianty (Jurnal Medika Nusantara, 2024)
This research was conducted with the aim of evaluating the effectiveness of morning sun exposure therapy in reducing bilirubin levels in newborns with physiological jaundice. The method used in this study is descriptive research with a case study approach. The study was carried out on a 3-day-old baby, Ny. N, after birth. The research took place at PMB Hasna Dewi, S.Keb, located on JL HR. Soebrantas, Kec. Tampan, Pekanbaru City in 2024. Data collection was done using both primary and secondary data. The data was gathered through interviews with Ny. N, direct observation, and physical examination of the baby. Based on this monitoring, the results of this study indicate that morning sun exposure therapy is proven to be an effective and safe alternative for helping to reduce bilirubin levels in newborns with physiological jaundice.